Mapping out a spectrum of the Chinese public's discrimination toward the LGBT community: results from a national survey - Yuanyuan Wang; Zhishan Hu; Ke Peng; Joanne Rechdan; Yuan Yang; Lijuan Wu; Ying Xin; Jiahui Lin; Zhizhou Duan; Xuequan Zhu; Yi Feng; Shitao Chen; et al. (BMC, 2020)
Abstract Background China has the world's largest lesbian, gay, bisexual, and transgender (LGBT) population. This study assessed the discrimination experienced by LGBT individuals in China in a comprehensive way, covering discrimination perpetrated by family, media, medical services, religious communities, schools, social services, and in the workplace. Methods The current study involved a national survey of 31 provinces and autonomous regions. Discrimination was measured both in terms of heterosexual participants' attitudes towards LGBT individuals, and LGBT participants' self-perceived discrimination. Pearson correlation analysis was performed to examine the difference between heterosexual participants' attitudes towards LGBT individuals and LGBT participants' self-perceived discrimination. Linear regression was used to investigate the association between gross domestic product per capita and discrimination. Results Among 29,125 participants, 2066 (7.1%) identified as lesbian, 9491 (32.6%) as gay, 3441 (11.8%) as bisexual, 3195 (11.0%) as transgender, and 10,932 (37.5%) as heterosexual. Heterosexual people were generally friendly towards the LGBT community with a mean score of 21.9 (SD = 2.7, total scale score = 100) and the grand averaged score of self-perceived discrimination by LGBT participants was 49.9 (SD = 2.5). Self-perceived discrimination from family and social services is particularly severe. We created a series of provincial level choropleth maps showing heterosexual participants' acceptance towards the LGBT community, and self-perceived discrimination reported by members of the LGBT community. We found that a higher level of economic development in provinces was associated with a decrease in discrimination, and we identified that every 100 thousand RMB increase in per capita GDP lead to a 6.4% decrease in discriminatory events perpetrated by heterosexuals. Conclusions Chinese LGBT groups consistently experience discrimination in various aspects of their daily lives. The prevalence of this discrimination is associated with the economic development of the province in which it occurs. In order to reduce discrimination, it is important for future studies to discover the underlying reasons for discrimination against LGBT individuals in China.